Comprehensive microarray-based analysis for stage-specific larval camouflage pattern-associated genes in the swallowtail butterfly, Papilio xuthus - Futahashi Ryo; Shirataki Hiroko; Narita Takanori; Mita Kazuei; Fujiwara Haruhiko (BMC Biology, 2012)
Abstract Background Body coloration is an ecologically important trait that is often involved in prey-predator interactions through mimicry and crypsis. Although this subject has attracted the interest of biologists and the general public, our scientific knowledge on the subject remains fragmentary. In the caterpillar of the swallowtail butterfly Papilio xuthus, spectacular changes in the color pattern are observed; the insect mimics bird droppings (mimetic pattern) as a young larva, and switches to a green camouflage coloration (cryptic pattern) in the final instar. Despite the wide variety and significance of larval color patterns, few studies have been conducted at a molecular level compared with the number of studies on adult butterfly wing patterns. Results To obtain a catalog of genes involved in larval mimetic and cryptic pattern formation, we constructed expressed sequence tag (EST) libraries of larval epidermis for P. xuthus, and P. polytes that contained 20,736 and 5,376 clones, respectively, representing one of the largest collections available in butterflies. A comparison with silkworm epidermal EST information revealed the high expression of putative blue and yellow pigment-binding proteins in Papilio species. We also designed a microarray from the EST dataset information, analyzed more than five stages each for six markings, and confirmed spatial expression patterns by whole-mount in situ hybridization. Hence, we succeeded in elucidating many novel marking-specific genes for mimetic and cryptic pattern formation, including pigment-binding protein genes, the melanin-associated gene yellow-h3, the ecdysteroid synthesis enzyme gene 3-dehydroecdysone 3b-reductase, and Papilio-specific genes. We also found many cuticular protein genes with marking specificity that may be associated with the unique surface nanostructure of the markings. Furthermore, we identified two transcription factors, spalt and ecdysteroid signal-related E75, as genes expressed in larval eyespot markings. This finding suggests that E75 is a strong candidate mediator of the hormone-dependent coordination of larval pattern formation. Conclusions This study is one of the most comprehensive molecular analyses of complicated morphological features, and it will serve as a new resource for studying insect mimetic and cryptic pattern formation in general. The wide variety of marking-associated genes (both regulatory and structural genes) identified by our screening indicates that a similar strategy will be effective for understanding other complex traits.